(untitled) (Ameghiniana, 2014)
New remains of Miocene cryptodiran turtles from the Chubut Valley near the town of Gaiman (Chubut Province) are described. Several isolated plates, collected in the basal section of the Gaiman Formation (Lower Miocene), represent the first record of Dermochelyidae in southem South America. An isolated humerus is referred 10 the Testudininae Chelonoidis cf. C. gringorum (Simpson, 1942); it was collected from the Trelew Member of the Sarmiento Formation, currently assigned to the Colhuehuapian Land Marnmal Age. The study of this humerus adds new information to the knowledge of this fossil taxon, and allows a specific differentation from C. chilensis Gray, 1870.